The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1073/pnas.89.13.6134
|View full text |Cite
|
Sign up to set email alerts
|

Contraction characteristics and ATPase activity of skeletal muscle fibers in the presence of antibody to myosin subfragment 2.

Abstract: To investigate the role of the myosin hinge region in muscle contraction, we examined the contraction characteristics and Mg-ATPase activity of glycerinated muscle fibers prepared from rabbit psoas in the presence and absence of polyclonal antibody directed against the subfragment 2 (S-2) region of myosin. The antibody-induced reduction of Ca2+-activated isometric force was always accompanied by a parallel decrease of muscle fiber stfess, so that the stiffness versus force relation remained unchanged by the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
56
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 22 publications
(23 reference statements)
4
56
0
Order By: Relevance
“…The large myosin head movement may not readily fit into the contraction model based on the myosin head rotation, and possibly would result either from cooperative action of myosin two heads (20,21) or from shortening of myosin subfragment-2 region (22,23). Much more experimental work is needed to clarify the myosin head movement responsible for muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
“…The large myosin head movement may not readily fit into the contraction model based on the myosin head rotation, and possibly would result either from cooperative action of myosin two heads (20,21) or from shortening of myosin subfragment-2 region (22,23). Much more experimental work is needed to clarify the myosin head movement responsible for muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors considered elastic bending of the long, light-chain-binding ␣-helix an obvious candidate (4,9,10). The actin-myosin interface (11) or the junction between the lightchain domain and the catalytic domain of the myosin head (9) as well as subfragment 2 were also considered (12) as other possibilities for the location of elastic distortion.…”
mentioning
confidence: 99%
“…Such melting would be expected to give rise to a reduction in the overall length of the molecule, and this is consistent with electron-microscope observations of the effect of temperature on the length of the myosin tail (Walker and Trinick, 1986;Walzthony et al, 1986). This transition could therefore be an important force-generating event in muscle contraction and the subfragment-2 region as well as the myosin head would contribute to force production in actively contracting muscle (Harrington et al, 1990;Sugi et al, 1992).It has recently been proposed that the myosin rod contains six independent domains (Privalov, 1982 ;Lopez-Lacomba et al, 1989;Bertazzon and Tsong, 1990). The Cterminus of the heavy chain has been shown to be unfolded and mobile , and to play a crucial role in myosin assembly Kalbitzer et al (1991) have indicated that the two chains are not in exact register but are slightly staggered.…”
mentioning
confidence: 99%
“…Such melting would be expected to give rise to a reduction in the overall length of the molecule, and this is consistent with electron-microscope observations of the effect of temperature on the length of the myosin tail (Walker and Trinick, 1986;Walzthony et al, 1986). This transition could therefore be an important force-generating event in muscle contraction and the subfragment-2 region as well as the myosin head would contribute to force production in actively contracting muscle (Harrington et al, 1990;Sugi et al, 1992).…”
mentioning
confidence: 99%